WORKING WITH A MULTICULTURAL SOCIETY - Rosita Tandos (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Along with the development process and globalization impact, the world recently becomes closer and inter-dependence. Responding such global situation, multiculturalism comes to offer solution for a wide range of issues associated with individual, cultural, ethnical and religious diversities. Understand this sense, multiculturalism is not an optional extra, or it is not something that society want to have it or avoid. For any societies, they need to work for manage diversity not sufficient with celebrating and acknowledging it. Then, social interventions and services at any aspects of life (social, cultural, education, economic and political) need to integrate the notion of integrity and diversity as parts of multiculturalism. This paper aims to introduce the need for understanding multiculturalism as a process that is always contextual, affecting significantly on community organizing and education programs.